New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae

Novel tetrazoloquinoline-thiazolidinone conjugates as possible antitubercular agents: synthesis and molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M. (Medchemcomm, 2016)
A novel approach for the synthesis of a new 4-thiazolidinone scaffold was developed by a one-pot three-component cyclocondensation of various tetrazolo quinoline aldehydes 1a-f, acid hydrazide 2a-c, and thioglycolic acid 3 in the presence of [DBUH].OAc] as a catalyst in high yields. All the conjugates were screened for their antimycobacterial activity against MTB H37Ra and M. bovis BCG strains, with the MIC values ranging from 0.99-13.55 mu mol mL(-1) and 0.14-20.11 mu mol mL(-1), respectively. The 4-thiazolidinone-incorporated tetrazoloquinoline derivatives 4a, 4d, 4g, 4j, 4m, and 4p were highly potent against MTB H37Ra and M. bovis BCG strains. The most active compounds were also evaluated for their cytotoxicity against MCF-7, A549, and HCT 116 cell lines and were found to be non-cytotoxic. Further, molecular docking studies into the active site of the InhA enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping us to understand the ligand-protein binding interaction and establish a structural basis for the inhibition of mycobacterium tuberculosis. The results suggest that the tetrazoloquinoline-thiazolidinone conjugates 4a, 4d, 4g, 4j, 4m, and 4p are promising antitubercular agents.

New bithiazolyl hydrazones: novel synthesis, characterization and antitubercular evaluation - Bhalerao, Mahendra B.; Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2017)
New bithiazolyl hydrazones (6a–l) have been first time synthesized by carrying novel one pot cyclocondensation of 5-acyl thiazoles (1a–b), thiosemicarbazide (2) and substituted phenacyl chlorides (4a–f) in freshly prepared ionic liquid, diisopropyl ethyl ammonium acetate (DIPEAc) at room temperature. The newly synthesized compounds have been evaluated for their antitubercular activity and the compounds 3b, 6a, 6b, 6d, 6e, 6f, 6g, and 6l have displayed noticeable antitubercular activity compared to Rifampicin with tolerable cytotoxicity. All these compounds were also screened for their antibacterial activity and found that, compounds 6j and 6k have exhibited a very good antibacterial activity. Molecular docking study has shown better harmony with the evaluation trend shown by these compounds under in vitro antitubercular screening.

Non nucleoside reverse transcriptase inhibitors, molecular docking studies and antitubercular activity of thiazolidin-4-one derivatives - Chitre, Trupti S.; Patil, Shital M.; Sujalegaonkar, Anagha G.; Asgaonkar, Kalyani D.; Khedkar, Vijay M.; Garud, Dinesh R.; Jha, Prakash C.; Gaikwad, Sharddha Y.; Kulkarni, Smita; Choudhari, Amit; Sarkar, Dhiman (Current Computer-Aided Drug Design, 2019)
Background: Management of Co-existence of Acquired immunodeficiency syndrome and Tuberculosis has become a global challenge due to the emergence of resistant strains and pill burden. Objective: Hence the aim of the present work was to design and evaluate compounds for their dual activity on HIV-1 and Tuberculosis (TB). Methods: A series of seven, novel Thiazolidin-4-one derivatives were synthesized and evaluated for their anti-HIV and anti-tubercular activity along with Molecular docking studies. All the seven compounds displayed promising activity against the replication of HIV-1 in cell-based assays. The four most active compounds were further evaluated against X4 tropic HIV-1(UG)(070) and R5 tropic HIV-1(vB59) primary isolates. The binding affinity of all the designed compounds for HIV-RT and Mycobacterium tuberculosis Enol Reductase (MTB InhA) was gauged by molecular docking studies which revealed crucial thermodynamic interactions governing their binding. Results: The CC50 values for the test compounds were in the range of, 15.08-34.9 mu g/ml, while the IC50 values were in the range of 16.1-27.13(UG(070); X4) and 12.03-23.64 (VB59; R5) mu g/ml. The control drug Nevirapine (NVP) exhibited CC50 value of 77.13 mu g/ml and IC50 value of 0.03 mu g/ml. Amongst all these compounds, compound number 3 showed significant activity with a TI value of 2.167 and 2.678 against the HIV-1 X4 and the R5 tropic virus respectively. In anti-mycobacterial screening, the compounds proved effective in inhibiting the growth of both log phase and starved MTB cultures. Conclusion: Compound 3 has been found to be active against HIV-1 as well as MTB.
Keywords: anti-HIV-1 activity; Antitubercular activity; human immunodeficiency virus-1; Molecular docking; Non nucleoside reverse transcriptase; thiazolidin-4-ones

New 1,2,3-triazole-appended bis-pyrazoles: synthesis, bioevaluation, and molecular docking - Danne, Ashruba B.; Deshpande, V, Mukund; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Shingate, Bapurao B. (ACS Omega, 2021)
The present work describes design of a small library of new 1,2,3-triazole-appended bis-pyrazoles by using a molecular hybridization approach, and the synthesized hybrids were evaluated for their antifungal activity against different fungal strains, namely, Candida albicans, Cryptococcus neoformans, Candida glabrata, Candida tropicalis, Aspergillus niger, and Aspergillus fumigatus. All the compounds exhibited broad-spectrum activity against the tested fungal strains with excellent minimum inhibitory concentration values. The molecular docking study against sterol 14 alpha-demethylase (CYP51) could provide valuable insights into the binding modes and affinity of these compounds. Furthermore, these compounds were also evaluated for their antioxidant activity, which also resulted in promising data.